2021
DOI: 10.1590/0102-311x00015920
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental trauma in Brazilian children and adolescents: a systematic review and meta-analysis

Abstract: This study aimed to investigate the prevalence of dental trauma in Brazilian children and adolescents. A systematic review was conducted considering eight databases: MEDLINE (via PubMed), LILACS, BBO, Scopus, Embase, Web of Science, Open Access Theses and Dissertations, and OpenThesis. Only prevalence studies that used a probabilistic sampling method were included, without restriction on year or language of publication. The JBI critical appraisal tools for prevalence studies were used to assess the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
12
1
1
Order By: Relevance
“…When studying the variables associated with trauma, only sex was significantly associated with injuries, which were more frequent in boys than in girls (p = 0.021; Table 2). Other studies have also shown a higher predisposition for men 10,[31][32][33] , which may be due to higher participation in contact sports, fights, automobile accidents, and more hyperactive habits and behavior 10,11 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…When studying the variables associated with trauma, only sex was significantly associated with injuries, which were more frequent in boys than in girls (p = 0.021; Table 2). Other studies have also shown a higher predisposition for men 10,[31][32][33] , which may be due to higher participation in contact sports, fights, automobile accidents, and more hyperactive habits and behavior 10,11 .…”
Section: Discussionmentioning
confidence: 94%
“…However, our results were lower than those of the last national epidemiological survey (20.5% 6 ) and other Brazilian studies (21.5% 7 ; 23.96% 8 ). Moreover, a meta-analysis showed an 18.1% 4 global dental trauma prevalence in 12-year-olds, and a recent systematic review found a 21% prevalence in Brazilian children and adolescents 10 . Distinct results may be due to regional differences, socioeconomic status, behavioral and phenotypic differences 10 , the criteria for recording dental trauma, sample size, study design, sampling, and randomization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many causes, such as falls, car accidents, sports, occupational accidents, or interpersonal violence can affect the dental arch and involve both teeth and their supporting tissues, causing functional, esthetic, and even psychological injury. [7][8][9][10][11] Each treatment is performed in accordance with the need of the case. Thus, the variability of traumatic injuries determines the diversity of treatments, which can be categorized as endodontic (pulpotomy, pulpectomy), restorative, periodontal (splinting of teeth), surgical (extractions), or as pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%